Geopolymer and green technology materials : selected, peer reviewed papers from the 2014 Malaysia-Indonesia Geopolymer Symposium (MIGS 2014), May 11-12, 2014, Kuala Lumpur, Malaysia - Al Bakri Abdullah, Mohd Mustafa (Materials science forum, 2014)
Collection of selected, peer reviewed papers from the 2014 Malaysia-Indonesia Geopolymer Symposium (MIGS 2014), May 11-12, 2014, Kuala Lumpur, Malaysia. The 57 papers are grouped as follows: Chapter 1: Aggregate, Chapter 2: Geopolymer Technology, Chapter 3: Green Materials, Chapter 4: Coating Keyword: Geopolymer, Green Technology, Materials, Engineering and Technology.